Diáspora, fronteiras e pós-colonialismo em os dois irmãos, de Germano Almeida - Cruz, Diego da (2018)
This work aims to analyze the work of Cape Verdean Germano Almeida The Two Brothers (1995) through the concepts of coloniality, colonization and culture. After analyzing the work, we will find that it establishes connection with Latin American works, especially Chronicle of a Death Foretold, by Gabriel Garcia Márquez, we will realize that there is a search for autonomy both in relation to writing and in the sociocultural sense of Cape Verde. In this work of Germano Almeida "[...] reality is confused with fiction". In this way, the plot could be a popular jury with or without evidence of a fratricide, but neither the narrator of the novel and reader is certain of the crime practiced by André. However, in this novel by Germano Almeida there are traces of that colony abandoned by Portugal, and damaged by economic decline, and highlights the Cape Verde diaspora, which makes Cape Verde a country with more inhabitants than inside the archipelago. Thus, will be briefly read with Willians (2007) and Mudimbe (2013) some transformations of the word culture and its implication the colonization of Africa. Soon after, with Said (2011) and Grosfoguel (2013), we will discuss the concept of "coloniality of power" and the search of the disciplines of cultural studies to collaborate in the search for new epistemologies. With Foucault (2001), we will highlight the implications of two characters (André who practices the crime of fratricide against his brother John) and the judge/narrator with the concept of "author function" in the process of "decolonization of power."